2022
DOI: 10.3390/antiox12010108
|View full text |Cite
|
Sign up to set email alerts
|

Life on Magnet: Long-Term Exposure of Moderate Static Magnetic Fields on the Lifespan and Healthspan of Mice

Abstract: All living organisms on the Earth live and evolve in the presence of the weak geomagnetic field, a quasi-uniform static magnetic field (SMF). In the meantime, although the effects of moderate and high SMFs have been investigated on multiple aspects of a living organism, a long-term SMF exposure of more than 1 year has never been reported. Here, we investigated the influence of a moderate SMF (70–220 mT head-to-toe) long-term continuous exposure (1.7 years) to two different SMF directions on healthy male C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, we exposed healthy mice continuously to 0.1–0.2 T SMF for 1.7 years and did not reveal harmful effects. 37 We also found that high SMFs of 9.4 T exposure for 200 h did not have observable defects in tumor‐bearing mice. 38 However, 14 h of prolonged treatment of gradient high SMFs had negative effects on type 1 and 2 diabetes mice, including spleen, hepatic, and renal tissue impairment.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For example, we exposed healthy mice continuously to 0.1–0.2 T SMF for 1.7 years and did not reveal harmful effects. 37 We also found that high SMFs of 9.4 T exposure for 200 h did not have observable defects in tumor‐bearing mice. 38 However, 14 h of prolonged treatment of gradient high SMFs had negative effects on type 1 and 2 diabetes mice, including spleen, hepatic, and renal tissue impairment.…”
Section: Discussionmentioning
confidence: 53%
“…Meanwhile, our group has published several articles about long‐term treatment with magnetic fields and found that SMFs do not have many safety issues for healthy mice. For example, we exposed healthy mice continuously to 0.1–0.2 T SMF for 1.7 years and did not reveal harmful effects 37 . We also found that high SMFs of 9.4 T exposure for 200 h did not have observable defects in tumor‐bearing mice 38 .…”
Section: Discussionmentioning
confidence: 67%
“…Most studies of SMFs have reported various beneficial effects, indicating their potentials in magnetotherapy. For example, we recently found that the exactly same sets of magnetic plates in this study not only can prolong the lifespan and health span of normally aged mice [ 41 ] but also can alleviate the kidney injury induced by cisplatin [ 42 ]. The guideline provided by World Health Organization (WHO) and International Commission on Non-Ionizing Radiation Protection (ICNIRP) set the safety threshold for the public exposure of SMF to 400 mT based on available research evidences [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioeffects of moderate and weak static magnetic fields: For a long time, the studies, investigating the biological effects of static magnetic fields, have usually focused on moderate and weak static magnetic fields (Driessen et al, 2020; Fan et al, 2022; Li et al, 2020; Rosen, 2003). Even though, based on these results, it cannot be clarified whether the biological effects of the static magnetic field are beneficial or harmful to human health (Driessen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%